2019
DOI: 10.21203/rs.2.19124/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abundant Taxa and Favorable Pathways in the Microbiome of Soda-Saline Lakes in Inner Mongolia

Abstract: Background: The chloride-carbonate-sulfate lakes (also called Soda-Saline lakes) are double-extreme ecological environments with high pH and high salinity values but can also exhibit high biodiversity and high productivity. The diversity of metabolic process that functioned well in such environments remains to be systematically investigated. Deep sequencing and species-level characterization of the microbiome in elemental cycling of carbon and sulfur will provide novel insights into the microbial adaptation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…We thank Dr. Wenyu Shi for data submission to NCBI and gcMeta. This manuscript was released as a preprint at Research Square (Zhao et al, 2019).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We thank Dr. Wenyu Shi for data submission to NCBI and gcMeta. This manuscript was released as a preprint at Research Square (Zhao et al, 2019).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…It was classi ed further into normal soda lake and soda-saline lake based on the concentration of sulfate or chloride [9]. It has been reported that class Halobacteria and Candidatus Nanohaloarchaeota were the abundant archaeal members in the hypersaline brine [10][11][12][13][14]. Both lineages were also predominant in the neutral saline lakes and saltern [14][15][16].…”
mentioning
confidence: 99%
“…Very recently, culture-dependent and -independent researches revealed that Ca. Nanohaloarchaeota had the capability of poly-or oligo-saccharide degradation in hypersaline brines of saltern and soda lakes [12,21]. Besides, the methylotrophic methanogenesis was evidently a dominant process, and many haloalkaliphilic methylotrophic methanogens were isolated from soda lakes, including Methanolobus, Methanosalsum, Methanocalculus and Methanonatronarchaeum [22,23].…”
mentioning
confidence: 99%
See 2 more Smart Citations